1970
DOI: 10.1136/jnnp.33.3.376
|View full text |Cite
|
Sign up to set email alerts
|

Seronegative dementia paralytica: report of a case

Abstract: SUMMARY Dementia paralytica may present diagnostic difficulties when routine serological test using a non-treponemal antigeni is non-reactive. We present an illustrative demented patient who initially had negative VDRL test both in his serum and cerebrospinal fluid. However, the brain biopsy specimen showed active meningoencephalitis. By

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1979
1979
2010
2010

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Indeed, Taveras and Wood (1976) indicated that general paresis frequently produces disproportionate enlargement of the cerebral subarachnoid space as compared with ventricular size, through cortical atrophy, though widening of cortical sulci and enlarged ventricles were occasionally found by others (Ch'ien et al, 1970;Venkoba Rao et al, 1972). Both these patterns were present in our control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, Taveras and Wood (1976) indicated that general paresis frequently produces disproportionate enlargement of the cerebral subarachnoid space as compared with ventricular size, through cortical atrophy, though widening of cortical sulci and enlarged ventricles were occasionally found by others (Ch'ien et al, 1970;Venkoba Rao et al, 1972). Both these patterns were present in our control group.…”
Section: Discussionmentioning
confidence: 99%
“…This is currently the most reliable laboratory test for the diagnosis of neurosyphilis (Escobar et al, 1970), and appears more sensitive than the treponemal immobilisation (TPI) and other quantitative flocculation tests (VDRL) which occasionally have been negative in pathologically proven dementia paralytica (Ch'ien et al, 1970).…”
Section: Discussionmentioning
confidence: 99%